Copper Binding Extrinsic to the Octarepeat Region in the Prion Protein - Walter, Eric D.; Stevens, Daniel J.; Spevacek, Ann R.; Visconte, Micah P.; Rossi, Andrew D.; Millhauser, Glenn L. (Current Protein and Peptide Science, 2009)
Current research suggests that the function of the prion protein (PrP) is linked to its ability to bind copper. PrP is implicated in copper regulation, copper buffering and copper-dependent signaling. Moreover, in the development of prion disease, copper may modulate the rate of protein misfolding. PrP possesses a number of copper sites, each with distinct chemical characteristics. Most studies thus far have concentrated on elucidating chemical features of the octarepeat region (residues 60-91, hamster sequence), which can take up to four equivalents of copper, depending on the ratio of Cu2+ to protein. However, other sites have been proposed, including those at histidines 96 and 111, which are adjacent to the octarepeats, and also at histidines within PrP's folded C-terminal domain. Here, we review the literature of these copper sites extrinsic to the octarepeat region and add new findings and insights from recent experiments.